Numerical modeling of residual stresses during vibratory peening of a 3-stage Blisk – a multi-scale discrete element and finite element approach - Alcaraz, Joselito Yam Tomacder (2022)
Vibratory-based manufacturing processes such as polishing, and peening are widely used for surface enhancement applications. Vibratory peening is an excellent process to introduce residual stresses, improve fatigue life, and enhance the surface quality of metallic components. This research aims to understand the combined peening-polishing mechanism in the vibratory peening process of a gas turbine engine's 3-stage blisk using a novel horizontal vibratory peening method. The research was aimed to understand the common understanding that the deeper the component in the vibratory machine, the higher would be the media-component interaction effect and better would be the peening effect. However, contrary to the hypothesis, the experimental findings showed significant peening (60.0 % higher than bottom) in the coupons near the top surface of the media in the trough. The DEM results revealed that the media-component normal relative velocity (Vn) and normal contact energy (Enc) contributed to the peening effect and the contact force (Fc), tangential contact energy (Etc) contributed to the polishing effect. The DEM results were used as input conditions for FEM to predict the residual stresses from peening. The FEM simulated residual stress trend matches the experimental findings, with differences not exceeding ∼ 40 % for most cases. The combined DEM-FEM approach provides an opportunity to understand the complex behavior of media-component interaction in a vibratory process. With this understanding, vibratory peening all three stages of a blisk simultaneously reduces the overall production cost and time.